Investigating the Association Between Gut Bacteria and Childhood Neuropsychiatric Disorders - Abdo, Maha (AUC Knowledge Fountain, 2024)
Background: The etiology of autism spectrum disorder (ASD) remains unclear. However, it’s believed to be a multifactorial condition. Several studies suggest the involvement of gut and oral microbiome in the predisposition of ASD symptoms. Understanding the pathophysiology could aid in developing better treatment strategies that improve the quality of life of ASD individuals and their caregivers. Aim: The current study aims at characterizing the gut and oral microbiome composition of ASD children compared to their healthy siblings and mothers as control groups. Methods: Stool and saliva samples were collected from fourteen families at Ain Shams University Hospital, Outpatient Clinic. The 16S rRNA V3-V4 hypervariable regions of the bacterial DNA extracted from the samples were sequenced and then analyzed using QIIME2 and R studio. Results: Several bacterial taxa belonging to phylum Actinobacteriota were differentially abundant in the study groups’ saliva and stool samples. Additionally, a reduction in butyrate-producing bacteria was seen in ASD stool samples. Conclusion: The current study provides evidence of altered microbiota composition in ASD children. However, future large-scale studies would give a better picture of the observed dysbiosis and possible ways to correct it.